Digital vigilantism and anti-paedophile activism in Russia: between civic involvement in law enforcement, moral policing and business venture - Favarel-Garrigues, Gilles (Global crime, 2020)
The rise of a reactionary political agenda in favour of traditional values led to the launching of an anti-paedophile campaign in Russia in the early 2010s. Taken on by ‘moral entrepreneurs’ well known by the general public for their familialist ideology and homophobic speeches, the issue of paedophilia was used to justify the adoption of legislative measures reinforcing a clampdown on child abuse and punishing those who disseminate propaganda about ‘non-traditional’ sexual relations to minors. This political agenda fuelled the emergence in Russian cities of self-proclaimed and competing ‘rule enforcers’, who began acting like vigilantes, setting traps for presumed paedophiles, purportedly in order to defend children. Contributing to a man-hunt atmosphere, these volunteers mix features of classical and digital vigilantism. However, they use digital tools not only to gather evidence or to publicise the identity of an alleged offender, but also to make a profit.